A qualitative study of decision-making and safety in ambulance service transitions - Rachel O’Hara; Maxine Johnson; Enid Hirst; Andrew Weyman; Deborah Shaw; Peter Mortimer; Chris Newman; Matthew Storey; Janette Turner; Suzanne Mason; Tom Quinn; Jane Shewan; et al. (Health Services and Delivery Research, 2014)
Background: Decisions made by front-line ambulance staff are often time critical and based on limited information, but wrong decisions in this context could have serious consequences for patients. There has been little research carried out in the ambulance service setting to identify areas of risk associated with decisions about patient care. Aim: The aim of this study was to qualitatively examine potential system-wide influences on decision-making in the ambulance service setting and to identify useful areas for future research and intervention. Methods: We used a multisite, multimethod qualitative approach across three ambulance service trusts. In phase 1 we carried out 16 interviews to contextualise the study and provide discussion points for phase 2. For phase 2, university and ambulance service researchers observed paramedics on 34 shifts and 10 paramedics completed ‘digital diaries’ that reported challenges to decision-making or to patient safety. Six focus groups were held, three with staff (n = 21) and three with service users (n = 23). From observation and diary data we developed a typology of decisions made at the scene. Data from these and other sources were also coded within a human factors framework and then thematically analysed to identify influences on those decisions. In phase 3, workshops were held at each site to allow participants and stakeholders (n = 45) to comment on the study findings. Participants were asked to rank influences on decisions using a ‘paired comparison’ method. Results: Interviews provided the context for further qualitative exploration. Nine types of decision were identified from observations and digital diaries, ranging from emergency department conveyance and specialist emergency pathways to non-conveyance. A synthesis of findings from the observations, diaries and staff focus groups revealed seven overarching system influences on decision-making and potential risk factors: meeting increasing demand for emergency care; impacts of performance regime and priorities on service delivery; access to appropriate care options; disproportionate risk aversion; education, training and professional development for crews; communication and feedback to crews; and ambulance service resources. Safety culture issues were also identified. Data from the service user focus groups reflected similar issues to those identified from the staff focus groups. Service user concerns included call handling and communication, triage, patient involvement in decisions, balancing demand, resources, access to care, risk aversion, geographical location and vulnerable patients. Group discussions highlighted a lack of awareness by the public of how best to use emergency and urgent care services. Workshop attendees were satisfied that the findings reflected relevant issues. The two issues ranked highest for warranting attention were staff training and development and access to alternative care. Conclusions: Multiple qualitative methods allowed a range of perspectives to be accessed and validation of issues across perspectives. Recommendations for future research include exploring effective ways of providing access to alternative care pathways to accident and emergency, assessing public awareness and expectations of ambulance and related services, exploring safe ways of improving telephone triage decisions and assessing the effects of different staff skill levels on patient safety. Funding: The National Institute for Health Research Health Services and Delivery Research programme.